CTL-Deep learning: Its influence on critical thinking skills and self-confidence in linear equation system material - Amelia Anggraini; Elly Arliani (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
Many senior high school students have difficulty in understanding Linear Equation Systems (LES). The Contextual Teaching and Learning-Deep Learning (CTL-DL) approach is one of the current solutions. This study aims to describe the effect of the CTL-DL approach on students' critical thinking skills and self-confidence in the material of Linear Equation Systems. This quasi-experimental study with a pretest-posttest control group design used a population of class X students of SMA Negeri 2 Yogyakarta in the 2024/2025 academic year. Sampling was carried out by purposive sampling. Data were collected using observation sheets, critical thinking ability tests, and self-confidence questionnaires, then analyzed using the Multivariate Hotelling's T² statistical test and the independent t-test at a significance level of 0.05. The results of the study showed: 1) there was an influence of the CTL-DL approach on students' critical thinking skills and self-confidence, 2) the CTL-DL approach was significantly superior to the expository approach in improving critical thinking skills, and 3) the CTL-DL approach was significantly superior to the expository approach in improving students' self-confidence